SOME ISSUES OF INTEGRATION OF THE INSTITUTION OF ARREST IN THE GENERAL LOGIC OF JUDICIAL CONTROL OVER THE FUNDAMENTAL RIGHT TO LIBERTY AND SECURITY - Melikyan, Ruben (State and Law, 2021)
In the article, the author discusses the issues of reforming the institution of arrest, presenting them under the imperative of ensuring the smooth implementation of the reforms. In particular, the pressing need of reformation of the institution of arrest, its theoretical and practical goals, and the main milestones of the reform process since the 2000s, as well as the need for all low-profile reforms in terms of effective implementation of the new mechanisms established by the 2021 Criminal Procedure Code are presented. The original solutions of the new code aimed at the more complete guarantee of the constitutional right to personal freedom are also discussed, as well as the theoretical and practical problems that are still unresolved under the new Code. Recommendations are made aiming at their solution.